Symptoms and Diagnostic Yields of Colonoscopy in St Vincentius Hospital Singkawang West Borneo 2017-2018 - Frandy Frandy; Prionggo Mondrowinduro (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Colonoscopy is the gold standard procedure which is widely used in the diagnosis and treatment of colonic mucosal disorder. Colonoscopy examination which is included in the referral system of the social insurance administration organization has been available at St Vincentius Hospital Singkawang since March 2017 to support diagnosis of lower gastrointestinal diseases. Patients were from Singkawang City and 3 surrounding districts (Sambas, Bengkayang, and Mempawah) that close to the Malaysian border. The purpose of this study is to evaluate symptom and diagnosis yield of patient who underwent colonscopy at St. Vincentius Hospital, Singkawang from March 2017 to April 2018.Method: This was a retrospective descriptive study by using secondary data of patient’s medical records at St Vincentius Hospital Singkawang in March 2017 - April 2018. Every patient is included as a sample (total sampling).Results: Total numbers are consisted 78 colonoscopies, with 163 cases of lower gastrointestinal disease. Three major findings of colonoscopy were internal hemorrhoids (64%), colon mass (30%), and inflammatory bowel disease (IBD) (26%). Indications of patient to underwent colonoscopy were hematochezia 38%, chronic diarrhea 19%, chronic constipation 18%, anemia 12%, abdominal pain 6%, screening neoplasia 3% and unexplained weight lost 3%.Conclusion: Hematochezia is the most common indication of patients to underwent colonoscopy at Singkawang and its surrounding districts. The most common finding of colonoscopy was hemorrhoid.